THE APPLICATION OF QUALITY FUNCTION DEPLOYMENT IN CAR SEAT INDUSTRY - Purba, Humiras Hardi; Sunadi, Sunadi; Suhendra, Suhendra; Paulina, Else (ComTech: Computer, Mathematics and Engineering Applications, 2020)
One of the things that are considered important for the car is the seat. Car seats could be able to give effect to the driver to be more comfortable. As in the research paper carried out in the car seat industry that is with two objectives defined, first to ensure that the right design of new products is based on customer needs with the Quality Function Deployment (QFD) approach and the second is to improve competitiveness based on renewal marketing strategies and customer needs such as longevity, no wrinkles, not easy to get dirty, no flat pillows, and competitive prices. Customer satisfaction ratings are used in this study to compare with competitors. Based on calculations using the QFD method, this shows that the seat option has the highest percentage of technical requirements in the car seat industry around 27.39%. The second factor is material about 25.94%, and then the third factor is the characteristic attenuation of about 19.17%. Therefore, for continuous quality improvement purposes in the future, still, a lot of customer needs regarding the seat car need to be developed, so further discussion is needed for the future researcher with a suggestion to use another method such as  Multi-Criteria Decision Making (MCDM), Analytical Network Process (ANP) or Analytical Hierarchy Process (AHP) to combine with Quality Function Development (QFD).